Determining the Accuracy of MRI in Evaluation of Infective Vertebral Lesions - Banjade, Udaya Raj; Kharel, Laxmi; Shrestha, Ashish; Ranabhat, Nawaraj; Shahi, Arun (Nepalese Journal of Radiology, 2023)
Introduction: MRI is highly accurate in identifying vertebral anomalies by detecting even the smallest changes in water and fat components, making it the preferred method for assessing infectious lesions in the vertebral column. Clinical observations and different imaging properties can help with early diagnosis and treatment. Vertebral endplate destruction, changes in the signal intensity of intervertebral disc and bone marrow, and involvement of the soft tissues surrounding the vertebrae are typical MRI findings of infectious vertebral lesions. Methods: To determine the diagnostic accuracy of MRI in patients suspected of having infective vertebral lesions, a cross-sectional study was conducted involving 52 individuals. The study compared the validity of MRI diagnosis with the diagnosis obtained through CT-guided fine needle aspiration cytology for infective vertebral lesions. Results: By comparing the MRI diagnoses with those of fine needle aspiration cytological diagnosis of vertebral lesions, the sensitivity, specificity, positive and negative predictive values (PPVs and NPVs), and ultimately diagnostic accuracy of MRI, were computed. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of MRI diagnosis for infective vertebral lesions were 95.6%, 71.4%, 95.6%, and 71.4%, respectively and 92.3% of diagnoses were made correctly overall. Conclusions: The finding of this study suggested that MRI should be considered to be the imaging modality of choice for patients with suspected infective vertebral lesions.